PENGARUH PROFITABILITAS TERHADAP LIKUDITAS MELALUI CAPITAL STRUCTURE PERUSAHAAN KOSMETIK Tbk PERIODE 2012-2016 - administrator administrator; Elyda Kurnia Pratiwi; Novrida Qudsi Lutfillah; Muninghar Muninghar (Prodi Magister Manajemen Universitas Wijaya Putra, 2019)
The purpose of this study is to prove and analyze the profitability of liquidity in companies in theIndonesia Stock Exchange for the period 2012-2016. Then to prove and analyze the profitability of thecapital structure of the company on the Indonesia Stock Exchange for the period 2012-2016. Next is toprove and analyze the capital structure of liquidity in companies in the Indonesia Stock Exchange for theperiod 2012-2016. This type of research is quantitative. The population and sample in this study were 6Cosmetic Companies on the Indonesia Stock Exchange for the period 2012-2016. The results in this studyindicate the profitability of the capital structure of companies in the Indonesia Stock Exchange for theperiod 2012-2016; liquidity towards the capital structure of companies in the Indonesia Stock Exchangefor the period 2012-2016; profitability is not towards the attitude of the company on the Indonesia StockExchange for the period 2012-2016.Keywords: profitability, liquidity, capital structure